Analysis of Managerial Performance of School Principals in the Implementation of Healthy Schools to Encourage Healthy Living Behavior - Sari, Wahyu Lita; Niswanto, Niswanto; Rasyid, Suparta (Journal La Edusci, 2025)
This study aims to analyze the managerial performance of school principals in the implementation of healthy school programs and its impact on the development of healthy living behaviors of students at SMA Negeri Bukit Bener Meriah. The background of this research is based on the importance of the role of school principals as leaders and education managers who are responsible for planning, implementing, and evaluating non-academic programs, including healthy school programs. This research uses a descriptive qualitative approach with a Research and Development (R&D) level 1 design. The data collection technique was carried out through observation, interviews, and documentation involving 12 informants, namely school principals, teachers, UKS coaches, coordinators of the Healthy School Movement (GSS), BK counselors, and students. The results of the study show that the principal has developed and implemented a healthy school program through healthy canteen activities, environmental cleanliness, health checks, routine exercise, and counseling on clean and healthy living behaviors (PHBS). Supporting factors for the implementation of the program include the commitment of the principal, teacher support, UKS coaches, and cooperation with the health center. However, there are obstacles in the form of limited infrastructure, low awareness among some students, the influence of modern lifestyles, and lack of parental support. Overall, the managerial performance of the principal at SMA Negeri 1 Bukit can be categorized as effective, while at SMA Negeri 2 Bukit still faces obstacles in the consistency of implementation. This research confirms that the success of healthy school programs is largely determined by visionary principal leadership, continuous oversight, and cross-sector collaboration.